Effects of acclimation on the haematological indices of different groups of fresh water teleosts (Journal of Applied and Natural Science, 2015)
Hematological parameters have been recognized as valuable tools for monitoring fish health. The aim of the present study was to obtain a basic knowledge of the hematological responses of different groups of fresh water teleosts during acclimation period. Haematological analysis was carried out in three different groups of teleosts namely Group I: Heteropneustes fossilis and Clarias gariepinus (Siluriformes), Group II: Anabas testudineus and Channa striatus (Perciformes), Group III: Labeo rohita and Cyprinus carpio (Cypriniformes). In all groups of teleosts, RBC and Hb were significantly (p